Eficiência de composto orgânico no desenvolvimento de mudas de Moringa oleifera LAM. - Gouvêia, Daniel Freitas Dantas (2020)
The practice of seedlings development has grown in Brazil, due to the need to recover degraded areas associated with the low cost of producing economic potential plant species. Moringa oleifera Lam. is a specie has many utilities as oil production, water purification, food function and recovery of areas was suffered degradation. In view of the above, this study aimed to evaluate the efficiency of organic compost produced by composting in the development of moringa seedlings. The experiment was conducted in a greenhouse at the UEFS Horto Florestal Experimental Unit. A randomized block design (DBC) was used, distributed in four blocks, with seven treatments and twenty and belt repetitions per block. The treatments were tested (1) commercial substrate; (2) (A) sand; (3) ((A) / Organic compound (CO) 80/20 sand; (4) (A:CO 60/40); (5) (A:CO 40/60); (6) (A:CO 20/80); (7) (A:CO 0/100). At 45 days after sowing the parameters were evaluated, plant height, neck diameter, number of leaves, height ratio to neck diameter, length and diameter of the tuberous root, shoot dry matter, root dry matter, root tuberose structure and total dry matter, Dickson's quality index, leaf area, in addition to the analysis of total protein, reducing sugars and total soluble sugars, chlorophyll and carotenoids. In commercial substrate, the seedlings showed a superior root tuberose structure and parameters height, neck diameter, shoot dry matter and leaf area reduced indicating stress during plant growth. For the parameters of height and number of leaves, the seedlings of the treatment A:CO 80/20, A:CO 60/40 and A:CO 40/60 were observed mean marbles and did not differ among themselves.For the biochemical parameters total soluble sugars and reducing sugars the commercial substratum treatments, A:CO 80/20, A:CO 60/40 and A:CO 40/60 were superior to the other treatments. Regarding total proteins, treatments with the proportions of organic compost were superior to other treatments. It’s concluded, therefore, that the A:CO 80/20 is the most suitable, as it presented good production of biomass and metabolites in a smaller proportion of the organic compost, promoting a better cost benefit for the producer.